EFFECT OF ORGANIC SOURCES OF NITROGEN FERTILIZATION ON GROWTH AND YIELD OF PEARL MILLET [Pennisetumglaucum (L.) R. BR. EMEND STUNTZ] - LAL CHAND YADAV; L. R. YADAV; SAROJ KUMARI YADAV (The Bioscan, 2020)
A field experiment was conducted at Agronomy farm, of S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif 2016 on loamy sand soil, which consisted fourten treatments of fertilizers/manures (control, FYM @ 125% of RDN, FYM @ 100% of RDN, FYM @ 75% of RDN, FYM @ 50% of RDN,VC @ 125 % RDN, VC @ 100% of RDN, VC @ 75% of RDN, VC @ 50% of RDN, PM @ 125% of RDN, PM @ 100% of RDN, PM @ 75% of RDN, PM @ 50% of RDN and 100% RDN through fertilizer) and were tested in randomized block design with three replications. Recommended dose of fertilizer for pearlmillet was 60 kg N and 30 kg P2O5/ha. Results indicated that application of VC @ 125% RDN, FYM @ 125% of RDN, FYM @ 100% of RDN, VC @ 100% of RDN, VC @ 75% of RDN, PM @ 125% of RDN, PM @ 100% of RDN and 100% RDN through fertilizer remaining at par with each other and significantly increased plant height, dry matter accumulation, total number of tillers, chlorophyll content effective tillers, ear length, grains per ear, test weight, grain, stover and biological yield, protein content over control. Phosphorus and potassium content in grain and stover were significantly increased due to application of VC @ 125% RDN